Konsepsi Negara Hukum Indonesia dalam Perspektif Hukum Progresif - M Muslih; S. Sahabudin (Universitas Batanghari Jambi, 2026)
The concept of the Indonesian Rule of Law, as stipulated in Article 1 paragraph (3) of the 1945 Constitution of the Republic of Indonesia, represents a Pancasila-based rule of law that is material and substantive, rather than merely formal. It is rooted in Pancasila values as the rechtsidee (legal ideal), emphasizing the supremacy of law, limitation of power, protection of human rights, as well as social justice and people’s welfare in the spirit of familial principles and mutual cooperation. From the perspective of Progressive Law introduced by Satjipto Rahardjo, this concept is enriched by the paradigm of “law for humans, not humans for law.” Progressive Law rejects rigid legal positivism and demands a dynamic, socially responsive approach, with the courage to make interpretive breakthroughs, prioritizing conscience, empathy, and substantive justice. Thus, the Indonesian Rule of Law becomes more vibrant, emancipatory, and capable of realizing the objectives of the state as stated in the Preamble to the 1945 Constitution. Progressive Law serves as a tool for revitalization so that the rule of law does not lose its moral conscience and truly serves the welfare and justice for all Indonesian people.